Association Between Tail-Biting and Intestinal Microbiota Composition in Pigs - Rabhi, Nassima; Thibodeau, Alexandre; Côté, Jean-Charles; Devillers, Nicolas; Laplante, Benoit; Fravalo, Philippe; Larivière-Gauthier, Guillaume; Thériault, William P.; Faucitano, Luigi; Beauchamp, Guy; Quessy, Sylvain (Frontiers in Veterinary Science, 2020)
Tail-biting (TB) is a serious behavioral disorder in pigs. It is defined as a pig biting the tail of another pig. It is an important challenge in swine production as it impacts the animal welfare, its health and the economics and safety of the pork meat supply chain. To prevent TB, some approaches have been proposed, including enrichment material and tail docking, but they are not optimal and leave unanswered questions. Nutrition appears to be an important factor in TB behavior, perhaps by modulating the intestinal microbiota (IM). Our aim was to assess an association between TB behavior and IM in pigs through comparisons of IM in groups of biter or bitten pigs to the IM in a non-biter/non-bitten negative control group, and through comparisons of IM between the biter and bitten groups. Each group, composed of 12 pigs, was formed at the beginning of the growing/finishing phase based on a target behavior analysis centered on TB behavior for the biter group and a score of damages caused to the tail for the bitten group. Fecal and blood samples were collected from each pig during a TB episode, at time 0, t0, and when the TB episode was considered finished, four weeks later, at time 1, t1. Serum cortisol level was determined by ELISA and used as an indicator of stress. The pig’s fecal microbiota was analyzed from DNA extracted from freshly collected fecal matter using amplicon sequencing of the V4 hypervariable region of the 16S rRNA gene. Serum cortisol levels were significantly higher in either the biter or bitten pig groups compared to the negative control group (p=0.02 and p=0.01, respectively). The microbiota alpha-diversity was not significantly different between all groups, biter, bitten and negative control. Analyses of beta-diversity, however, revealed a significant difference between either the biter or the bitten group in comparison to the non-biter/non-bitten negative control group in terms of structure and composition of the microbiota. Lactobacillus were significantly more abundant in the negative control group compared to the two other groups (p=0.001). No significant difference was revealed between the biter and bitten groups.